(untitled) (Proceedings of the International Conference on Public Health, 2021)
Background. Schistosomiasis has been a community health problem in endemic areas. In Indonesia, it is caused by trematode Schistosoma japonicum, with snail Oncomelania hupensis lindoensis as its intermediate host. This disease is only found in three endemic areas in Central Sulawesi Province: Napu and Bada highlands, Poso Regency, and Lindu highland in Sigi Regency. Various schistosomiasis control efforts were accomplished for more than the last twenty years. However, the schistosomiasis prevalence in Indonesia still fluctuates. The study aimed to determine the effectiveness of the Peda’ team in the research area. Method. One strategy of schistosomiasis control by community empowerment, namely the Bada Model, was implemented in Bada highland, Poso Regency, Central Sulawesi Province, from May to November 2019. One of the model’s elements is the formation of the schistosomiasis control village team (namely Peda’ Team), which was trained about schistosomiasis control. After the training, they were assigned several duties, including schistosomiasis socialization to the village community, stool sample collection, snail habitat control, snail and rats survey, and assisting the mass drug administration. The evaluation was conducted in stool sample coverage and the snail habitat area. Results. The results showed an increase in stool sample collection coverage in the community, becoming more than 80% in almost all endemic villages. We found the decrease from 26 become three focus areas because of the active effort to control the schistosomiasis intermediate snail focus area. Based on the results can be concluded that the Peda team formation can support schistosomiasis control more useful in the research area